Peranan Intervensi Fisioterapi Metode Senam Kegel Untuk Mengatasi Kegagalan Kerja Sel Otot Polos Pada Kelainan Kandung Kemih Inkontinensia Urin - Argorby Simanullang; Naomi Dwany; Ruth Y. Purba; Melany Djami; Wahyu Irawati (Jurusan Biologi FMIPA Universitas Cenderawasih, 2021)
Urinary incotinensia is a disease that causes sufferers to experience urine without realizing it or is often referred to as bed-wetting. Urinary incotinence causes sufferers to experience difficulty or sleep disturbances, depression, isolation, lack of confidence, irritability, limiting social activities, and spending a lot of money on medication so that they really need a treatment solution. Urinary incontinence results from weakening of the smooth muscle in the bladder organs. One of the treatments that can be done to overcome urinary incontinence is using physiotherapy, namely by doing Kegel exercises. The purpose of this paper is to determine the role of physiotherapy interventions using Kegel exercises to overcome the failure of smooth muscle cells in urinary incontinence bladder disorders. This literature review will discuss four focus studies, namely: 1) the structure and function of the renal organ system, 2) the structure and working mechanism of smooth muscle cells, 3) cellular studies of urinary incontinence, and 4) treatment of urinary incontinence using physiotherapy interventions. Physiotherapy with Kegel exercises has the benefit of strengthening the work of the bladder sphincter and pelvic floor muscles. The mechanism is by increasing smooth muscle cell metabolism. The metabolic rate of the muscles will increase the strength of the smooth muscle and the nervous system to contract, so that the smooth muscle will get stronger. However, Kegel exercises do not completely cure urinary incontinence and only relieve the symptoms it causes.Key words: Physiotherapy; Urinary incontinence; Smooth muscles; Cells; Kegel exercises.